Development of a new analytical approach based on cellulose membrane and chelator for differentiation of labile and inert metal species in aquatic systems - Rosa, André Henrique [UNESP]; Bellin, I. C.; Goveia, D.; Oliveira, L. C.; Lourenco, R. W.; Dias, N. L.; Burba, P. (Elsevier B.V., 2006)
A new procedure was developed in this study, based on a system equipped with a cellulose membrane and a tetraethylenepentamine hexaacetate chelator (MD-TEPHA) for in situ characterization of the lability of metal species in aquatic systems. To this end, the DM-TEPHA system was prepared by adding TEPHA chelator to cellulose bags pre-purified with 1.0 mol L-1 of HCl and NaOH solutions. After the MD-TEPHA system was sealed, it was examined in the laboratory to evaluate the influence of complexation time (0-24 h), pH (3.0, 4.0, 5.0, 6.0 and 7.0), metal ions (Cu, Cd, Fe, Mn and Ni) and concentration of organic matter (15, 30 and 60 mg L-1) on the relative lability of metal species by TEPHA chelator. The results showed that Fe and Cu metals were complexed more slowly by TEPHA chelator in the MD-TEPHA system than were Cd, Ni and Mn in all pH used. It was also found that the pH strongly influences the process of metal complexation by the MD-TEPHA system. At all the pH levels, Cd, Mn and Ni showed greater complexation with TEPHA chelator (recovery of about 95-75%) than did Cu and Fe metals. Time also affects the lability of metal species complexed by aquatic humic substances (AHS); while Cd, Ni and Mn showed a faster kinetics, reaching equilibrium after about 100 min, and Cu and Fe approached equilibrium after 400 min. Increasing the AHS concentration decreases the lability of metal species by shifting the equilibrium to AHS-metal complexes. Our results indicate that the system under study offers an interesting alternative that can be applied to in situ experiments for differentiation of labile and inert metal species in aquatic systems. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: water; natural organic matter; metals; lability; humic substances